The Influence of Digital Marketing Strategy and Brand Image on Npure Skincare Repurchase - Nadia, Nanda; Nurhadi, Nurhadi (Dinasti Publisher, 2025)
The purpose of this study is to analyze the influence of digital marketing strategies and brand image on the repurchase of Npure skincare products on Shopee customers in Surabaya. This study uses a quantitative method with an associative approach with the aim of testing the relationship between variables, namely with digital marketing functioning as an independent variable, brand image functioning as an intermediate variable, and repurchase functioning as a bound variable. The non-probability sampling technique was applied in the determination of the sample by considering the criteria of respondents aged 18-25 years, active Shopee users, and have purchased Npure products at least twice. Primary data was analyzed through the distribution of an online questionnaire with a likert scale and processed using the SmartPLS 4.0 application by testing the realism, validity, R-Square calculation, and hypothesis using the bootstrapping method. The findings of this study indicate that brand image is strongly influenced by digital marketing (T-statistics = 15,217 > 1.96) and repurchases (T-statistics = 2,194 > 1.96). Furthermore, brand image also significantly influences consumers' decision to make a repeat purchase (T-statistic = 8.632 > 1.96). However, brand image does not play a role as a mediating variable for digital marketing and repurchase strategies (T-stats = 1.716 < 1.96). These findings confirm that effective digital marketing strategies, such as the use of social media, attractive promotional content, consistent interaction with consumers, are able to improve brand image and encourage customer loyalty through repeat purchases.